Case report: Bilateral renal ectopy with bilateral accessory renal artery and renal pelvis variations - Abdoul Mouïnou Poudiougo; Tata Touré; Babou Ba; Abdoulaye Kanté; Moumouna Koné; Gaoussou Simpara; Falé Traoré; Issoufou Ramdane; Moustapha Dicko; Nouhoun Ongoïba (Elsevier, 2023)
Introduction: Renal ectopia also known as ectopic kidney is an embryological renal abnormality characterized by abnormal anatomical location of one or both kidneys. Kidneys can vary in number, shape, size, position, rotation and vascularization. These variations are of immense importance due to their susceptibility to trauma, infection and iatrogenic injury.We reported the first case of bilateral renal ectopia associated with a bilateral accessory renal artery, a retro-aortic left renal vein and a variation of the renal pelvis. Case report: During a routine dissection of a male cadaver, showing no trace of trauma or surgical scar in the abdomen, we observed a rare case of bilateral renal ectopia and bilateral accessory renal artery. The left renal vein was retro-aortic and anastomosed with the left common iliac vein. We also observed the right renal vein drained the testicular vein, the fusion of the major calyxes (formation of the renal pelvis) outside the right kidney. These observations are of paramount importance to interventional radiologists, nephrologists and vascular surgeons. Conclusion: Renal vasculature variations are common in the population and are important not only for surgeons, but for radiologists. Therefore, a good knowledge of the multiple variations of renal vessels and renal ectopia is important for urologists and radiologists when performing kidney surgeries in kidney donors and transplants, in the end to avoid otherwise to reduce the rate of haemorrhage by accidental lesions of the accessory arteries during surgeries involving the kidneys in particular.